Question practice: the personal-assistant mock job interview - McLean, Terence (My University, 2024)
This activity is one way for students to practice forming questions in English as they engage in a fun, communicative task: The Personal-Assistant Mock Job Interview. It should follow lessons on asking and answering questions in English as well as using modals and expressions of ability (can, able to, etc.). Students will have learned about forming yes/no and Wh- questions. Especially, students should be introduced to how Wh- questions are formed, depending on what information they are looking for (the subject or the object): Q: Why do you want this job? (looking for the object—the reason), Q: Who can work evenings? (looking for the subject—the person), Q: When are you available to start working? (be verb following the Wh- question word).
Keywords: English as a second language; job interviews; interview questions